Current status of non‐invasive prenatal testing in Japan. Issue 8 (6th June 2017) - Samura, Osamu; Sekizawa, Akihiko; Suzumori, Nobuhiro; Sasaki, Aiko; Wada, Seiji; Hamanoue, Haruka; Hirahara, Fumiki; Sawai, Hideaki; Nakamura, Hiroaki; Yamada, Takahiro; Miura, Kiyonori; Masuzaki, Hideaki; et al.
Abstract: Aim: The purpose of this study was to report the 3‐year experience of a nationwide demonstration project to introduce non‐invasive prenatal testing (NIPT) of maternal plasma for aneuploidy, and review the current status of NIPT in Japan. Methods: Tests were conducted to detect aneuploidy in high‐risk pregnant women, and adequate genetic counseling was provided. The clinical data, test results, and pregnancy outcomes were recorded. We discuss the problems of NIPT on the basis of published reports and meta‐analyses. Results: From April 2013 to March 2016, 30 613 tests were conducted at 55 medical sites participating in a multicenter clinical study. Among the 30 613 women tested, 554 were positive (1.81%) and 30 021 were negative (98.1%) for aneuploidy. Of the 289, 128, and 44 women who tested positive for trisomies 21, 18, and 13, respectively, and underwent definitive testing, 279 (96.5%), 106 (82.8%), and 28 (63.6%) were determined to have a true‐positive result. For the 13 481 women with negative result and whose progress could be traced, two had a false‐negative result (0.02%). The tests were performed on the condition that a standard level of genetic counseling be provided at hospitals. Conclusion: Here, we report on the 3‐year nationwide experience with NIPT in Japan. It is important to establish a genetic counseling system to enable women to make informed decisions regarding prenatal testing. Moreover, a welfare system is warranted to support women who decide to give birth to and raise children with chromosomal diseases.